2013
DOI: 10.1093/carcin/bgt224
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study of the proapoptotic effect of tolfenamic acid: involvement of NF- B activation

Abstract: Recent studies demonstrate that tolfenamic acid (TA) induces apoptosis and suppresses the development and progression of several types of cancers. However, the underlying mechanisms are complex and remain to be fully elucidated. Nuclear factor-kappaB (NF-κB) plays a critical role in inflammation, cancer development and progression. Although non-steroidal anti-inflammatory drugs modulate NF-κB signaling pathway in different ways, the link between NF-κB and TA-induced apoptosis of colorectal cancer cells has yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…6). Indeed, we observed that TA activates NF-jB transcriptional activity [45] and ATF3 activation, which is required for TA-induced apoptosis [15]. NF-jB is a key mediator of the cellular stress response and activation of NF-jB can induce apoptosis [46].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…6). Indeed, we observed that TA activates NF-jB transcriptional activity [45] and ATF3 activation, which is required for TA-induced apoptosis [15]. NF-jB is a key mediator of the cellular stress response and activation of NF-jB can induce apoptosis [46].…”
Section: Discussionmentioning
confidence: 83%
“…Previously, we reported that TA-stimulated apoptosis is associated with up-regulation of pro-apoptotic proteins, early growth response-1 (EGR-1) and activating transcription factor 3 (ATF3) [14,15]. In terms of NF-jB activation, we also reported that TA increases nuclear p65 translocation through IKK-mediated translocation and p65 accumulation through a novel mechanism involving proteosomal degradation and cooperation of p65 with p53 [45]. Therefore, the present study demonstrates that TA-stimulated ROS generation may play a significant upstream role by targeting various cancer-associated proteins and contribute TAinduced apoptosis in cancer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, pretreatment of MRBE dose-dependently inhibited LPS-induced p65 nuclear translocation in RAW264.7 cells. There is a growing evidence that NF-κB activation is modulated by ERK1/2 activation [24]. Thus, we evaluated the effects of MRBE on phosphorylation of ERK1/2 in LPS-stimulated RAW264.7 cells using Western blot to further investigate whether inhibition of NF-κB activation by MRBE was associated with modulation of ERK1/2.…”
Section: Resultsmentioning
confidence: 99%
“…We found anticancer therapy (Verma, 2004;Kim et al, 2006). However, some reports suggest that NF-κB activation by aspirin and tolfenamic acid promotes a proapoptotic response in cancer cells (Stark et al, 2001;Jeong et al, 2013). Although tolfenamic acid induces NF-κB activation in human colorectal cancer cell line, HCT116, it has been reported that tolfenamic acid suppresses inflammatory stimuli-mediated NF-κB signaling pathway in HCT116 cells (Shao et al, 2015).…”
Section: Discussionmentioning
confidence: 83%